⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ N = j = 1 ∑ 1 7 2 8 j ( j − 1 7 2 7 ) M = k = 1 ∑ ∞ 7 k + 1 k ( k + 1 ) 6 k + 7
For N and M as defined above, find the remainder when M M N + 1 is divided by 1000.
The problem is original.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
M = k = 1 ∑ ∞ 7 k + 1 k ( k + 1 ) 6 k + 7 = k = 1 ∑ ∞ 7 k + 1 k ( k + 1 ) 6 ( k + 1 ) + 1 = k = 1 ∑ ∞ 7 k + 1 1 ( k 6 + k ( k + 1 ) 1 ) = k = 1 ∑ ∞ 7 k + 1 1 ( k 6 + k 1 − k + 1 1 ) = k = 1 ∑ ∞ 7 k + 1 1 ( k 7 − k + 1 1 ) = k = 1 ∑ ∞ ( 7 k k 1 − 7 k + 1 ( k + 1 ) 1 ) = 7 1
N = j = 1 ∑ n j ( j − ( n − 1 ) ) = j = 1 ∑ n j 2 − ( n − 1 ) j = 1 ∑ n j = 6 n ( n + 1 ) ( 2 n + 1 ) − ( n − 1 ) ⋅ 2 n ( n + 1 ) = 2 n ( n + 1 ) ( 3 2 n + 1 − ( n − 1 ) ) = − 6 n ( n + 1 ) ( n − 4 ) = − 6 1 7 2 8 ( 1 7 2 9 ) ( 1 7 2 4 ) = − 2 8 8 ( 1 7 2 9 ) ( 1 7 2 4 ) Let n = 1 7 2 8
Therefore,
M M N + 1 ≡ N + M 1 (mod 1000) ≡ − 2 8 8 ( 1 7 2 9 ) ( 1 7 2 4 ) + 7 (mod 1000) ≡ − 2 8 8 ( 7 2 9 ) ( 7 2 4 ) + 7 (mod 1000) ≡ − 2 8 8 ( 2 7 1 ) ( 2 7 6 ) + 7 (mod 1000) ≡ − 2 8 8 ( 2 5 0 + 2 1 ) ( 2 5 0 + 2 6 ) + 7 (mod 1000) ≡ − 1 8 ( 1 0 0 0 + 8 4 ) ( 1 0 0 0 + 6 9 ) + 7 (mod 1000) ≡ − 1 8 ( 8 4 ) ( 1 0 4 ) + 7 (mod 1000) ≡ − 1 8 ( 1 0 0 − 1 6 ) ( 1 0 0 + 4 ) + 7 (mod 1000) ≡ − 1 8 ( − 1 2 6 4 ) + 7 (mod 1000) ≡ 1 8 ( 2 6 4 ) + 7 (mod 1000) ≡ 4 7 5 2 + 7 (mod 1000) ≡ 7 5 9 (mod 1000)